Cortical GABA levels are reduced in young adult binge drinkers: Association with recent alcohol consumption and sex - Ksenija Marinkovic; Austin B. Alderson Myers; Donatello Arienzo; Martin I. Sereno; Graeme F. Mason (NeuroImage: Clinical, 2022)
Binge drinking refers to a pattern of alcohol intake that raises blood alcohol concentration to or above legal intoxication levels. It is common among young adults and is associated with health risks that scale up with alcohol intake. Acute intoxication depresses neural activity via complex signaling mechanisms by enhancing inhibition mediated by gamma-amino butyric acid (GABA), and by decreasing excitatory glutamatergic effects. Evidence primarily rooted in animal research indicates that the brain compensates for the acute depressant effects under the conditions of habitual heavy use. These neuroadaptive changes are reflected in neural hyperexcitability via downregulated inhibitory signaling, which becomes apparent as withdrawal symptoms. However, human evidence on the compensatory reduction in GABA signaling is scant. The neurochemical aspect of this mechanistic model was evaluated in the present study with proton magnetic resonance spectroscopy (1H-MRS) which is sensitive to GABA plus macromolecule signal (GABA + ). Furthermore, we examined sex differences in GABA + levels as a function of a recent history of binge drinking, given interactions between endogenous neurosteroids, GABA signaling, and alcohol.The study recruited young adult women and men (22.2 ± 2.8 years of age) who were classified as binge drinkers (BDs, N = 52) if they reported ≥ 5 binge episodes in the previous six months. Light drinkers (LDs, N = 49) reported drinking regularly, but not exceeding ≤ 2 binge episodes in the past six months. GABA-edited 1H-MR spectra were acquired from the occipital cortex at 3 T with the MEGA-PRESS sequence. GABA + signal was analyzed relative to water and total creatine (Cr) levels as a function of binge drinking history and sex. Controlling for within-voxel tissue composition, both GABA + indices showed decreased GABA + levels in BDs relative to LDs. The reduced GABA + concentration was associated with occasional high-intensity drinking in the BD group.This evidence is consistent with compensatory GABA downregulation that accompanies alcohol misuse, tipping the excitation/inhibition balance towards hyperexcitability. Analysis of the time course of GABA + neuroplasticity indicated that GABA + was lowest when measured one day after the last drinking occasion in BDs. While the BD vs LD differences were primarily driven by LD women, there was no interaction between Sex and a history of binge drinking. GABA + was higher in LD women compared to LD men.Aligned with the allostasis model, the mechanistic compensatory GABA downregulation observed in young emerging adults engaging in occasional binge drinking complements direct neural measures of hyperexcitability in BDs. Notably, these results suggest that neuroadaptation to alcohol is detectable at the levels of consumption that are within a normative range, and may contribute to adverse health outcomes.